How Far has Islamic Business Ethic been Researched? - Antonio, Muhammad Syafii (SMART Insight, 2023)
This study aims to investigate trends and developments in scholarly publications on Islamic business ethics, focusing on documents indexed in the Scopus database. The total data analyzed involved 333 documents, which came from various journal sources. The analytical method used was a bibliometric approach, and the analysis was conducted using Biblioshiny R software. The results showed that there were fluctuations and an increasing trend in the publication of publications on Islamic business ethics every year. The number of articles discussing this theme is quite significant, indicating an increasing interest and contribution in academic literature related to Islamic business ethics. Authors from various countries participate in publishing articles on this topic, and Malaysia is identified as the most productive country in this regard. Many journals published articles on this theme, and the Journal of Islamic Marketing (JIMA) was one of the most impactful, with many authors researching this topic and using various keywords. The most frequently used keywords include